Reward and Punishment to Motivate Performance in Islamic Perspective - Abdul Mun’im; Renny Oktafia; Taufiq Churrahman (Proceedings of The ICECRS, 2020)
In Islamic education, the granting of punishment and reward is permitted based on the Quran and Sunnah by maintaining aspects of tarbiyah. This study aims to discuss how effective the application of reward and punishment systems in motivating someone's performance in general, be it students, employees. And as a religious individual, especially for those who are Muslim, how does the effect of implementing this reward and punishment system increase faith and good deeds or avoid evil. This research uses a descriptive qualitative approach. Data collection techniques include library research, observation, and documentation. Data analysis techniques are data reduction, and data verification. The results showed that the forms of rewards given included rewarding someone who excelled in an action, were able to improve the person's performance motivation in the future and could motivate others to do the same good.On the other hand, punishment is also important to apply including giving advice and guidance, showing a sour face, giving a hard rebuke, and giving additional tasks, such as memorizing the surah or short verses from the Quran or hadith, is also able to prevent someone from doing negative things and try not to repeat negative things in the future.